1999
DOI: 10.1023/a:1006159016703
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Ki‐67 and topoisomerase IIα expression in infiltrating ductal carcinoma of the breast

Abstract: To evaluate the prognostic relevance of Ki-67 and topoisomerase IIalpha expression in relation to tumor stage, grade, and hormone receptor content, 942 ductal infiltrating carcinomas of the breast were examined by means of the monoclonal antibodies Ki-S11 (Ki-67) and Ki-S4 (topoisomerase IIalpha). pS2, c-erbB2, and p53 were additionally considered as prognostic variables. The median follow-up time was 149 months. Eight-hundred-and-sixty-three tumors reacted with Ki-S11 and Ki-S4; the labeling indices of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 45 publications
9
31
2
1
Order By: Relevance
“…Contrary to previous results from our group (Rudolph et al, 1999a) and others (Jarvinen et al, 1996(Jarvinen et al, , 1998Rudolph et al, 1999b), we failed to observe a significant positive correlation between Topo IIa expression and Her-2/neu-overexpression in this series. Approximately 50% of the Her-2/neu overexpressing tumours in our series contained high levels of Topo IIa, whereas in the remaining 50%, Topo IIa was low (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to previous results from our group (Rudolph et al, 1999a) and others (Jarvinen et al, 1996(Jarvinen et al, , 1998Rudolph et al, 1999b), we failed to observe a significant positive correlation between Topo IIa expression and Her-2/neu-overexpression in this series. Approximately 50% of the Her-2/neu overexpressing tumours in our series contained high levels of Topo IIa, whereas in the remaining 50%, Topo IIa was low (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…In line with the proliferation-specific expression of Topo IIa (Kellner et al, 1997(Kellner et al, , 2002, we observed a highly significant correlation between Ki-S7 and Ki-67, which was also reported by others (Depowski et al, 2000;Rudolph et al, 1999a;Tuccari et al, 1993), in addition to a strong link between the number of Topo IIa-expressing cells and the S-phase fraction of the cell cycle (Jarvinen et al, 1996;Sandri et al, 1996a). Given the known association between high tumour cell proliferation and chemosensitivity (Tannock, 1978;Belembaogo et al, 1992;O'Reilly et al, 1992), one might suspect the observed therapy response to be related to the proliferative activity of the tumours.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Different antibodies were used through all trials: anti-Ki-67 was used in 24 studies (52.1%), anti-MIB-1 in 24 studies (52.1%), both antibodies were performed in five studies (Keshgegian and Cnaan, 1995;Veronese et al, 1995;Bevilacqua et al, 1996;Querzoli et al, 1996;Billgren et al, 2002), anti-Ki-S5 in two studies (Rudolph et al, 1999a;Esteva et al, 2004) and anti-Ki-S11 in one study (Rudolph et al, 1999b). The different cut-off values used were those of the authors (range: 3.5 -34%).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The proliferation fraction of the invasive component (i.e. not including ductal carcinoma in situ) of the tumour cells outside lymph vessels (PF-T), was scored using a method similar to that described by Potemski et al and by Rudolph et al [37,38]. First the tumour fields with highest reactivity for MIB-1 were selected and then the number of MIB-1 positive tumour nuclei was counted in 500 tumour cells and this gave the percent of the proliferating tumour cells (500 tumour cells were present in 2-3 high magnification fields, 9400 according to amount of tumoural stroma).…”
Section: Assessment Of Lymphangiogenic and Angiogenic Characteristicsmentioning
confidence: 99%